Jenatsch's Axe : Social Boundaries, Identity, and Myth in the Era of the Thirty Years' War - Head, Randolph Conrad (Book collections on Project MUSE., 2008)
In this engaging volume, Randolph C. Head traces the career of an extraordinarily adaptable and ruthless seventeenth-century figure, George Jenatsch (1596-1639). Born a Protestant pastor's son, Jenatsch's career took him from the clergy to the military to.